2012
DOI: 10.5606/tgkdc.dergisi.2012.044
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pulsatile flow characteristics on hemolysis, transfusion requirement, and hemostasis in open heart surgeries

Abstract: Bu çalışmanın amacı, pulsatil ve pulsatil olmayan perfüzyonun hemoliz parametreleri ve kan komponentlerinin korunması üzerindeki etkilerini araştırmaktır. Ça lış mapla nı:Randomize kontrollü ve prospektif olarak tasarlanmış bu çalışmaya, açık kalp ameliyatı yapılan 27 pulsatil olmayan (NP) ve 24 pulsatil (P) olgudan oluşan iki bağımsız grup dahil edildi. Demografik ve hemodinamik veriler kaydedildi. Perfüzyon türlerinin etkisi serbest hemoglobin (serbest Hb), haptoglobin (Hp), laktat dehidrogenaz (LDH), potasy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…One of the most important factors limiting pulsatile flow usage is that pulsatile flow may cause hemolysis. Recently, however, Silistreli et al [19] reported that this type of flow does not cause clinically significant hemolysis. In our study, we did not observe significant hemolysis or thrombocytopenia, and the number of transfused erythrocyte cell units was also similar in our two groups.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors limiting pulsatile flow usage is that pulsatile flow may cause hemolysis. Recently, however, Silistreli et al [19] reported that this type of flow does not cause clinically significant hemolysis. In our study, we did not observe significant hemolysis or thrombocytopenia, and the number of transfused erythrocyte cell units was also similar in our two groups.…”
Section: Discussionmentioning
confidence: 99%